THE ROLE OF QOLBU MANAGEMENT IN BUILDING IDEAL MUSLIM PERSONALITY - Abid Nurhuda (JURNAL HURRIAH: Jurnal Evaluasi Pendidikan dan Penelitian, 2022)
Human personality is not something that can be obtained instantly but is a form of a combination of processes that occur around the world ranging from family, work, play, school, and also social. He is awakened from 3 things, namely the mind, body and heart. The heart itself in Arabic is usually called the Qalbu which functions to be the mover as well as the king for all members of the body. Later on the day of qiyamat will be held accountable for both outward and inward actions so that the purpose of this study is to describe how the role of heart management in building the ideal Muslim personality. The method used is literature with primary data, namely the book jagalah hatimu and syarah 10 muwasofat, while the secondary data are books, ebooks, articles and supporting journals are accompanied by a note-taking technique during collection, then the contents are analyzed and followed by concluding. The results of the role of qolbu management in building an ideal Muslim personality include maximizing the potential for creed safety, perfecting the authenticity of worship, confirming the nobility of morality, strengthening body health, clearing the mind, exercising independence, putting things in order, maintaining punctuality, empowering benefits for people others and determined to fight lust.